The Significance of The Jadids’ Scientific Heritage In Developing The Spirituality of Youth In New Uzbekistan - kizi, Samadova (Indonesian Journal Publisher, 2025)
This article discusses the scientific heritage of the enlightened Jadids, their views on education and upbringing, and their significance in developing the spirituality of the youth, who are the builders of New Uzbekistan today. This study explores the enduring significance of the Jadids’ scientific heritage in fostering spirituality among youth in New Uzbekistan. The research employs a qualitative methodology, including historical and textual analysis, to examine the contributions of prominent figures like Mahmudkhodja Behbudi and Abdulla Avloni. Results highlight that the Jadids’ reforms in education, such as establishing new-method schools and promoting national consciousness, continue to influence modern strategies for youth development. The findings underline the importance of integrating their values into contemporary educational frameworks to nurture spiritually mature and socially responsible individuals. In conclusion, the study reaffirms that the Jadids’ legacy serves as a vital blueprint for cultivating well-rounded youth, essential for building New Uzbekistan.